WOM and SENTIMENT Analysis Has Positive Influence to Positive or Negative Emotion from Class 11 or 12 in Jakarta and Surrounding Area - Hendra Achmadi (Fakultas Ekonomi Dan Bisnis Universitas Pelita Harapan, 2022)
College selection is one of the decision-making processes in life that must be passed by high school students, the influence of WOM (Word of Mouth) and SENTIMEN Analysis originating from social media Twitter does it affect positive and negative emotions that arise when students This high school student listens to college offers from marketing. The influence of WOM in this study is from two sources, namely the influence of parents and the second is the influence of friends. Meanwhile, the SENTIMEN analysis was taken from 105 universities' social media twitter, while the emotional factor was taken from the PANAS scale. Primary data retrieval to 105 respondents from 11th and 12th grade high school students by using Google forms, while secondary data SENTIMEN analysis uses python program to 105 universities with 100 tweets so that the tweet data taken is 10500 tweets, and by using natural language processing then positive, neutral and negative sentiments can be distinguished. Then data processing using PLS-SEM. And from the results of data processing, it was found that WOM and SENTIMEN had a positive effect on positive emotion of R2 by 15.3% and negative emotion by R2 of 17.4%. SENTIMEN analysis had no effect on positive emotion and negative emotion.